The Prioritization of Dehstans of MeshkinShahr County in tems of Agricultural Development Surfaces - Vakil Heydari Sarban (نشریه جغرافیا و برنامه‌ریزی, 2012)
The world experiments show that agricultural section is important from point of view food stuff supply, employment generation, currency provision and supply of the other economic sections such as industrial activities and also the role that has on the national gross production. Also capabilities and local and regional relative advantages on every rural region is different by reason of making an effect from different economic, social and environmental views including the wherewithal and condition of demography, production, geography, climate, infrastructure etc. This important result comes out in that some rural regions by reason of agricultural development having superiority in relation to other regions. Also the cognition of local and regional advantages and capabilities each rural region is the fundamental principle of rural and agricultural planning. Until capabilities, capacities and rural regions advantages are considered for the agricultural development any region had its special planning for developmental purposes. The purpose of the present study was to prioritize Meshkinshahr Dehstans in terms of agricultural development aspects. The methodological approach was a descriptive–analytical survey type. Statistical population consisted of all farmers in Meshkinshar County. The sample size was determined by using Cockran formula (n=185). The content and face validity of the instrument was specified after several reviews and correction by the faculty members of the University and several expertise of administrative offices. A pilot test was conducted to determine the reliability of questionnaires and Cronbach Alpha coefficient of 0.82 was achieved. The achieved data was analyzed by TOPSIS technique. The assumption was that the good quality of every index evenly is rising (or declining). As the matter of fact the best existence value from each index indicates positive ideals and the worst existence value from that index indicates negative ideals. Also indexes are detached from each other. At the end, the results of multi-attribute decision making methods in the base of calculated weights showed that Dehestans of Meshkine Shargi and Garasou were located in the first rank in view of agricultural developemnt, respectively, and Dehestans of Nogdou were positioned in the last rank. Finally, based on the results of analysis, some applied recommendations have been provided